Motivation: The Key to Improve Students’ Outcomes - Vo, Ha (Issues in Language Instruction, 2018)
Most students in Vietnam have been exposed to English since the third grade. However, their outcomes are still limited due to a lack of motivation to study English. This presentation will suggest a number of policies to improve student achievement.